Running economy and blood lactate accumulation in elite football players with high and low maximal aerobic power - Nilsson, J.; Cardinale, D. (LASE Journal of Sport Science, 2015)
The purpose was to determine running economy and lactate threshold among a selection of male elite football players with high and low aerobic power. Forty male elite football players from the highest Swedish division ("Allsvenskan") participated in the study. In a test of running economy (RE) and blood lactate accumulation the participants ran four minutes each at 10, 12, 14, and 16 kmoh-1 at horizontal level with one minute rest in between each four minutes interval. After the last sub-maximal speed level the participants got two minutes of rest before test of maximal oxygen uptake (VO2max). Players that had a maximal oxygen uptake lower than the average for the total population of 57.0 mL O2okg-1ominute-1 were assigned to the low aerobic power group (LAP) (n=17). The players that had a VO2max equal to or higher than 57.0 mL O2okg-1ominute-1 were selected for the high aerobic power group (HAP) (n=23). The VO2max was significantly different between the HAP and LAP group. The average RE, measured as oxygen uptake at 12, 14 and 16kmoh-1 was significantly lower but the blood lactate concentration was significantly higher at 14 and 16 kmoh-1for the LAP group compared with the HAP group.